Sollen CEOs rotieren? - Bruno S. Frey; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2021)
Die Institution eines einzelnen CEO (Chief Executive Officer) hat erhebliche Schwächen. Der CEO hat andere Interessen als die Eigentümer und deren Vertreter sowie die anderen Topmanager. Einer einzelnen Person so viel Macht zuzuweisen ist riskant. Der Wechsel eines CEO verursacht hohe Kosten. Jedoch hat auch die traditionelle Alternative - ein kollektiv arbeitendes Top- Management-Team - Nachteile. Eine neue Governance-Institution - ein Team von rotierenden Chief Executive Officers - vereint die Vorteile der beiden traditionellen Modelle, ohne mit deren Nachteilen behaftet zu sein. – – The institution of a single CEO (Chief Executive Officer) has significant weaknesses. The CEO's interests diverge from those of the owners and their representants as well as other top managers. Assigning so much power to a single person is risky. Changing a CEO incurs high costs. However, the traditional alternative, a top management team working collectively, also has serious drawbacks. A new governance institution - a team of rotating chief executive officers - combines the advantages of the two traditional models without being fraught with their disadvantages.
Keywords: 330; Governance; CEO; board of directors; supervisory board; management team; CEO; Verwaltungsrat; Aufsichtsrat; Rotation